Mitigating effects of sea-level rise on maritime features through the international law-making process in the Law of the Sea - Chen, Xidi; Xu, Qi (Frontiers in Marine Science, 2022)
Sea-level rise is not only causing physical damage to maritime features but also posing challenges to the law of the sea. The United Nations Convention on the Law of the Sea lends legal significance to the relative position of the land and the sea. However, the ecological situation of maritime features and rising sea levels are changing these factors and placing the legal status of these features at risk of reclassification. This implies that islands with full rights may lose their exclusive economic zones, continental shelves, and even territorial seas due to sea-level rise. In addition to the physical enhancement of maritime features, legal solutions, as a more sustainable and affordable approach, are expected to contribute to mitigating adverse impacts of sea-level rise. However, most discussions are limited to the issue of baselines and maritime boundaries, while the legal status of maritime features has not received sufficient attention. In this paper, we examine in detail the limitations of existing laws, particularly the Convention, and present substantive and procedural options for the establishment of new rules to mitigate the effects of sea-level rise. The legal impacts of sea-level rise on maritime features can be categorized into three different aspects: dynamics of the relative position of land and sea, ecological degradation, and human interventions. It was found that the current international rules are insufficiently flexible in addressing the challenges posed by sea-level rise; thus, international law-making is therefore considered necessary. As far as the proposed rule is concerned, either legally “sustaining” the status of maritime features or allowing reclassification elicits complex issues, particularly considering the close connection between land and maritime zones under the law of the sea. Moreover, attempts to achieve new rules by applying any procedural option for international law-making in isolation may be impractical. In light of this, we explore a viable approach to the progressive development of relevant legal regimes, following the international community’s optimal consensus and shared interests.